2014
DOI: 10.3347/kjp.2014.52.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Ticks Collected from Wild and Domestic Animals and Natural Habitats in the Republic of Korea

Abstract: Ticks were collected from 35 animals from 5 provinces and 3 metropolitan cities during 2012. Ticks also were collected by tick drag from 4 sites in Gyeonggi-do (2) and Jeollabuk-do (2) Provinces. A total of 612 ticks belonging to 6 species and 3 genera were collected from mammals and a bird (n=573) and by tick drag (n=39). Haemaphyalis longicornis (n=434) was the most commonly collected tick, followed by H. flava (158), Ixodes nipponensis (11), Amblyomma testudinarium (7), H. japonica (1), and H. formosensis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…When two models were considered together, eight significant variables overlapped for predicting both the distribution of the H. longicornis and SFTS cases, including elevation, precipitation of warmest quarter, annual mean temperature, mean diurnal range of temperature, livestock density, mammalian richness, population density and rainfed croplands, although different relative contributions of them were found in restraining their distributions. These factors are generally reflective of the environments where wild and/or domestic animal hosts exist and enable tick survival, virus circulation and adequate exposure of human hosts to the virus [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…When two models were considered together, eight significant variables overlapped for predicting both the distribution of the H. longicornis and SFTS cases, including elevation, precipitation of warmest quarter, annual mean temperature, mean diurnal range of temperature, livestock density, mammalian richness, population density and rainfed croplands, although different relative contributions of them were found in restraining their distributions. These factors are generally reflective of the environments where wild and/or domestic animal hosts exist and enable tick survival, virus circulation and adequate exposure of human hosts to the virus [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these results reflect the complicated tick-borne pathogen epizootology reported throughout the wide geographical range of I . persulcatus [ 22 , 47 , 48 ]. These ticks therefore represent a pathogen transmission risk for both dogs and humans [ 49 ] and results of this study confirm the risk of tick-borne disease transmission from I .…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, some studies have serologically identified Borrelia in dogs, and the seroprevalence ranges between 1.1% and 2.2% [12,35,36]; however, Borrelia infection in dogs has not been molecularly proven. Haemaphysalis longicornis is known as a dominant tick species in Korea, and other tick species, including Ixodes, Amblyomma, and Rhipicephalus, have been identified in different environments [37,38]. The fact that I. nipponensis is not a dominant tick species in dogs and in environments in Korea [38] might be the reason for the low seroprevalence of Lyme borreliosis in dogs in this country.…”
Section: Discussionmentioning
confidence: 97%